2011
DOI: 10.1186/cc10037
|View full text |Cite
|
Sign up to set email alerts
|

Circulating soluble urokinase plasminogen activator receptor is stably elevated during the first week of treatment in the intensive care unit and predicts mortality in critically ill patients

Abstract: IntroductionsuPAR is the soluble form of the urokinase plasminogen activator receptor (uPAR), which is expressed in various immunologically active cells. High suPAR serum concentrations are suggested to reflect the activation of the immune system in circumstances of inflammation and infection, and have been associated with increased mortality in different populations of non-intensive care patients. In this study we sequentially analyzed suPAR serum concentrations within the first week of intensive care in a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
317
8
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 263 publications
(360 citation statements)
references
References 31 publications
30
317
8
5
Order By: Relevance
“…The ROC-AUC for mortality of suPAR was comparable to previous investigations in ventilated critically ill patients, which could have included many patients with ARDS [6][7][8]. However, the ROC-AUC was low, which could at least in part be because of the high mortality in these patients.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The ROC-AUC for mortality of suPAR was comparable to previous investigations in ventilated critically ill patients, which could have included many patients with ARDS [6][7][8]. However, the ROC-AUC was low, which could at least in part be because of the high mortality in these patients.…”
Section: Discussionsupporting
confidence: 74%
“…However insightful, additional measurement of suPAR over time did not fit within the design of this study, aimed at maximum relevancy for use in clinical practice. Furthermore previous research has demonstrated suPAR levels to be stably elevated during the entire first week on the ICU [6]. Finally, combining suPAR with clinical severity scores did not improve the ROC-AUC, yet many other biological markers have been reported as possibly useful in the prediction of mortality in ARDS.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, expression and release of uPAR is upregulated by a number of proangiogenic or proatherogenic growth factors, cytokines such as IL-1, and vascular endothelial growth factor, suggesting its involvement in proliferative and inflammatory processes (23). Koch et al demonstrated the prognostic impact of serum suPAR levels during the clinical course within the first week in a large cohort of critical adult patients in a medical intensive care unit (24). Sarafidis et al showed that infants with BPD have an early persistent inflammatory response (25).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases in which suPAR is proposed as a marker of inflammation, CRP and suPAR are positively correlated with each other. 13,14 In parallel with the suPAR measurements, serum CRP was determined to assess the inflammatory status in a randomly selected subset of patients from both the FSGS CT and PodoNet cohorts as well as in controls. The average CRP levels were generally low, indicating minimal inflammation, and there was no difference between controls and FSGS patients (Figure 2A).…”
Section: C-reactive Protein In Fsgs Patientsmentioning
confidence: 99%